Short RNAs: How Big Is This Iceberg? - Rigoutsos, I. (Current Biology, 2010)
Recent studies have reported the identification of piwi-associated RNAs (piRNAs) in Drosophila somatic cells. Interestingly, these piRNAs derive from the 3' untranslated regions of a subset of transcribed protein-coding genes and, experimentation suggests, might control the expression of other protein-coding transcripts. Studies of additional organisms support the new pathway's presence across animals.